Phosphorylation of influenza A virus NS1 protein at threonine 49 suppresses its interferon antagonistic activity - Kathum, Omer Abid (Cell Microbiol, 2016)
Phosphorylation and dephosphorylation acts as a fundamental molecular switch that alters protein function and thereby regulates many cellular processes. The non‐structural protein 1 (NS1) of influenza A virus is an important factor regulating virulence by counteracting cellular immune responses against viral infection. NS1 was shown to be phosphorylated at several sites; however, so far, no function has been conclusively assigned to these post‐translational events yet. Here, we show that the newly identified phospho‐site threonine 49 of NS1 is differentially phosphorylated in the viral replication cycle. Phosphorylation impairs binding of NS1 to double‐stranded RNA and TRIM25 as well as complex formation with RIG‐I, thereby switching off its interferon antagonistic activity. Because phosphorylation was shown to occur at later stages of infection, we hypothesize that at this stage other functions of the multifunctional NS1 beyond its interferon‐antagonistic activity are needed.